Long-term association of remnant cholesterol with all-cause and cardiovascular disease mortality: a nationally representative cohort study - Chen, Min; Chen, Zhi; Ye, Huarong; Cheng, Yuanling; Jin, Zhigang; Cai, Shaoqian (Frontiers in Cardiovascular Medicine, 2024)
Background and objectives Despite reducing low-density lipoprotein cholesterol (LDL-C) to the normal range, residual cardiovascular risk remain. Remnant cholesterol (RC) exerts a potential residual risk for cardiovascular disease (CVD) prevention, and the long-term longitudinal association between RC and mortality has yet to be well elucidated. Methods This study examined a nationally representative sample of 13,383 adults aged 20 years or older (mean age 45.7 and 52% women) who participated in the NHANES III (from1988 to1994). Causes of death were ascertained by linkage to death records through December 31, 2019. The relations of RC with all-cause and CVD mortality were tested using weighted Cox proportional hazard models. Results Through a median follow-up of 26.6 years, 5,044 deaths were reported, comprising 1,741 deaths of CVD [1,409 deaths of ischemic heart disease (IHD) and 332 deaths of stroke] and 1,126 of cancer. Compared to those with RC <14.26 mg/dl (lowest quartile), participants with RC ≥29.80 mg/dl (highest quartile) had multivariable-adjusted HRs of 1.23 (95% CI: 1.07–1.42) for all-cause mortality, 1.22 (95% CI: 0.97–1.53) for CVD mortality, and 1.32 (95% CI: 1.03–1.69) for IHD mortality, and 0.89 (95% CI: 0.55–1.43) for stroke mortality, and 1.17 (95% CI 0.90–1.52) for cancer mortality. We observed that elevated RC levels increased CVD risk and IHD mortality despite LDL-C being in the normal range. Conclusions Elevated blood RC was associated with an increased long-term risk of all-cause, CVD, and IHD mortality. These associations were independent of socioeconomic factors, lifestyles, and history of diseases, and remained robust across the LDL-C stratum. Measuring RC levels might favor clinical assessment of early CVD risk. Further investigation is needed to elucidate the optimal range of RC levels for cardiovascular disease health in the general population.